2022
DOI: 10.37363/bnr.2022.33115
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Nurses in Using Critical-Care Pain Observation Tools to Assess Pain of Unconscious Patient in Intensive Care Unit

Abstract: Introduction: In the critical nursing area, many intubated patients are unable to communicate to indicate the level of pain felt. Assessing the characteristics of pain, especially in patients with mechanical ventilation is a major nursing intervention that requires nursing knowledge. The examination of the CPOT pain scale was certainly accompanied by the knowledge that must be possessed by the nurse when going to conduct a pain assessment in patients who were not able to express pain verbally in the ICU, so as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Most recent debate has concluded that challenges by nurses are knowledge deficits, negative attitudes, inadequate record keeping, poor patient assessment, and improper analgesic use [14], [13], [15], [16], [17], [18]. Even using pain scales has shown to have poor knowledge [19].…”
Section: Introductionmentioning
confidence: 99%
“…Most recent debate has concluded that challenges by nurses are knowledge deficits, negative attitudes, inadequate record keeping, poor patient assessment, and improper analgesic use [14], [13], [15], [16], [17], [18]. Even using pain scales has shown to have poor knowledge [19].…”
Section: Introductionmentioning
confidence: 99%